Merger policy in innovative industries - González-Maestre, Miguel (2018)
We analyze optimal merger policy in R&D-intensive industries with product innovation aiming to improve the quality of products. Our results suggest that a permissive merger policy is rarely optimal in high-tech industries when the antitrust authority considers a welfare standard that balances the impact of mergers on con- sumers’ surplus and firms’ profits. In particular, relative to a benchmark where the effects from R&D are absent, we show that the optimal merger policy should not be substantially more permissive in the presence of those effects from R&D.